Fever in a paraplegia patient with a pressure ulcer - Meheroz H. Rabadi, MD, MRCPI, FAAN, FANA (Radiology Case Reports, 2021)
The incidence rates of pressure ulcers (PUs) in patients with SCI in the United States varies by clinical setting, ranging from 0.4%-38% in acute care, 2.2%-23.9% in long-term care, and 0%-17% in home care [1,2]. Unrelieved pressure is the most important factor in the development of PUs. Other factors associated with PUs in patients with SCI include age at the time of injury, men, blacks, completeness of the injury, functional dependence, behavioral protective factors such as frequent pressure relief, self-positioning, daily skin monitoring, nutritional state, cigarette smoking, alcohol (ab)use, and being depressed [3]. Presence of PUs affects functional physical outcomes; thus, prevention of PUs is the key [4]. Infection is a common complication of PUs which can be local such as cellulitis or osteomyelitis or systemic such as septicemia with a greater than 50% mortality. We present a case of a 58-year-old paraplegic man with pressure ulcer who presented with fever in the presence of an osteomyelitis and had a pelvic abscess on magnetic resonance imaging which needed surgical drainage.